Iron, aluminum, and thorium impurity removal from a rare earth element pregnant leach solution using magnesium carbonate - Sicheng Li; Maziar E. Sauber; Tong Sun; Gisele Azimi (Scientific Reports)
Abstract This study investigates the selective precipitation of aluminum, iron, and thorium from a rare earth element (REE)-containing pregnant leach solution (PLS) using magnesium carbonate (MgCO3) as a precipitant. The goal is to efficiently remove impurities while minimizing valuable REE losses. A combination of experimental methods and aqueous thermodynamic modeling (OLI software) was used to understand the precipitation behavior of these elements under varying pH, temperature, and hydrogen peroxide (H2O2) conditions. Kinetic experiments confirmed equilibrium is reached within 30 min. A central composite design (CCD) and response surface methodology (RSM) revealed that iron is nearly completely removed at pH 3.5, with thorium and aluminum precipitation occurring at higher pH values. Optimal conditions, 81 °C, pH 3.6, and 0.52 mL H2O2, enabled complete removal of iron, ~ 95% removal of thorium, and ~ 65% of aluminum, with TREE losses under 3%. Solid precipitates were characterized via X-ray diffraction, Raman spectroscopy, inductively coupled plasma mass spectroscopy, and scanning electron microscopy energy dispersive spectroscopy, identifying ferrihydrite, aluminum sulfate, and magnesium carbonate phases. Thermodynamic models supported experimental findings, qualitatively predicting solubility trends. A technoeconomic analysis for a 1000 m3/day PLS treatment plant in Ontario, Canada, estimated monthly operational costs at ~$2.65 million and capital costs at ~$7.85 million. This work advances impurity removal strategies in REE processing, offering scalable, cost-effective, and environmentally responsible solutions for enhancing REE recovery efficiency.